1970
DOI: 10.3329/jom.v10i3.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Coma Scale following Acute Stroke and In-hospital Outcome: An Observational Study

Abstract: Acute stroke is a heterogeneous condition and the risk of death can be gauged by various factors. This study sought to evaluate GCS score on admission as a prognostic tool of outcome among stroke patients, by observing the GCS score following acute stroke and in-hospital outcome at a tertiary level hospital in Bangladesh. Stroke is a major health problem in developed countries as well as developing countries like Bangladesh. This observational study was conducted among 122 consecutive patients, fulfilling the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
2
Order By: Relevance
“…This finding is similar with that of Hayee et al (1998) where 57.2% were male and rest 42.8% were female. [7] But this result differs with the study of (Miah et al, 2009) where 70.49% were male and 29.51% were female. [8] Hypertension is major risk factor for intracerebral hemorrhage in general, it is commonly considered to be associated with deep hemorrhage.…”
Section: Table13contrasting
confidence: 55%
See 1 more Smart Citation
“…This finding is similar with that of Hayee et al (1998) where 57.2% were male and rest 42.8% were female. [7] But this result differs with the study of (Miah et al, 2009) where 70.49% were male and 29.51% were female. [8] Hypertension is major risk factor for intracerebral hemorrhage in general, it is commonly considered to be associated with deep hemorrhage.…”
Section: Table13contrasting
confidence: 55%
“…[7] But this result differs with the study of (Miah et al, 2009) where 70.49% were male and 29.51% were female. [8] Hypertension is major risk factor for intracerebral hemorrhage in general, it is commonly considered to be associated with deep hemorrhage. In present study 70% of patients had hypertension, which was the commonest risk factor of stroke.…”
Section: Table13contrasting
confidence: 55%
“…The GCS score is the most widely used indicator of the severity of consciousness disturbance ( 40 ). Many studies have shown that the GCS score was associated with a poor prognosis ( 41 , 42 ). Patients with LHI usually demonstrate a severe disturbance of consciousness ( 43 ) and for patients with LHI, the baseline GCS score at admission has been significantly associated with death ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…FOUR score developed for assessment of consciousness in medical illness has been found to be better than GCS because this score also assesses brainstem and respiration in addition to motor and eye response of GCS. Various other Scales like Scandevian Stroke Scale, European Stroke scale, are extensively validated and used for research and clinical use [2][3].…”
Section: Introductionmentioning
confidence: 99%